CVPDr DNA FRAGMENT AFFECT DIFFERENCES IN RESISTANT TO CITRUS VEIN PHLOEM DEGENERATION (CVPD) DISEASE, NUTRIENT DEFICIENCIES AND QUALITY OF FRUITS - I Gusti Ayu Diah Yuniti; I Gede Putu Wirawan; I Nyoman Wijaya; Made Sritamin (International Journal of Biosciences and Biotechnology, 2017)
Citrus Vein Phloem Degeneration (CVPD) disease is a major obstacle in the effort to develop and increase the production of citrus fruits in Bali. The study on the polymorphism of CVPDr DNA fragment shows that the CVPDr DNA fragment is resistant factor againt CVPD disease. This study try to elaborate the difference in resistance led to differences in plant nutrients deficiencies in the citrus plant with CVPD disease. . Besides, there are also difference in the quality of fruit due to CVPD disease attacks such as water content, vitamin C content and antioxidants in citrus fruits, color, flavor, taste and texture and fruit into small, hard and sour taste.